Control and performance analysis of a single-stage utility-scale grid-connected PV system - Lal V.N.; Singh S.N. (My University, 2025)
For utility-scale photovoltaic (PV) systems, the control objectives, such as maximum power point tracking, synchronization with grid, current control, and harmonic reduction in output current, are realized in single stage for high efficiency and simple power converter topology. This paper considers a high-power three-phase single-stage PV system, which is connected to a distribution network, with a modified control strategy, which includes compensation for grid voltage dip and reactive power injection capability. To regulate the dc-link voltage, a modified voltage controller using feedback linearization scheme with feedforward PV current signal is presented. The real and reactive powers are controlled by using dq components of the grid current. A small-signal stability/eigenvalue analysis of a grid-connected PV system with the complete linearized model is performed to assess the robustness of the controller and the decoupling character of the grid-connected PV system. The dynamic performance is evaluated on a real-time digital simulator. © 2007-2012 IEEE.